Infiltration, runoff and soil loss in Andisols affected by forest fire (Canary Islands, Spain). Issue 19 (15th June 2012) - Neris, J.; Tejedor, M.; Fuentes, J.; Jiménez, C.
Abstract: Depending on the severity of the fire, forest fires may modify infiltration and soil erosion processes. Rainfall simulations were used to determine the hydrological effects of fire on Andisols in a pine forest burned by a wildfire in 2007. Six burned zones with different fire severities were compared with unburned zones. Infiltration, runoff and soil loss were analysed on slopes of 10% and 30%. Forest floor and soil properties were evaluated. Unburned zones exhibited relatively low infiltration (23 and 16 mm h −1 on 10% and 30% slope angles, respectively) and high average runoff/rainfall ratios (43% and 50% on 10% and 30% slope angles, respectively), which were associated with the extreme water repellency of the forest floor. Nonetheless, this layer seems to provide protection against raindrop impact and soil losses were found to be low (8 and 16 g m −2 h −1 for 10% and 30% slope angles, respectively). Soil cover, soil structure and water repellency were the main properties affected by the fire. The fire reduced forest floor and soil repellency, allowing rapid infiltration. Moreover, a significant decrease was noted in soil aggregate stabilities in the burned zones, which limited the infiltration rates. Consequently, no significant differences in infiltration and runoff were found between the burned and the unburned zones. The decrease in post‐fire soil cover and soil stability resulted in order‐of‐magnitude increases in erosion. Sediment rates were 15 and 31 g m −2 h −1 on the 10% and 30% slope angles, respectively, in zones affected by light fire severity. In the moderate fire severity zones, these values reached 65 and 260 g m −2 h −1 for the 10% and 30% slope angles, respectively. Copyright © 2012 John Wiley & Sons, Ltd.